2011
DOI: 10.1007/s11663-011-9511-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal Anode Performance in Low-Temperature Electrolytes for Aluminum Production

Abstract: An investigation has been undertaken into the performance of metal alloy anodes used to produce aluminum via an electrochemical method. Alumina was electrolyzed in NaF/AlF 3 and KF/AlF 3 electrolytes and mixtures thereof with copper-nickel-iron (Cu:Ni:Fe) alloy anodes and titanium diboride (TiB 2 ) cathodes. The operating temperatures of the electrochemical cells ranged from 973 K to 1123 K (700°C to 850°C), with an anode current density of 5000 A/m 2 . Cells ranged in current capacity from 10 to 300 amperes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…This diffusion leads to the creation of pores and voids in the wüstite layer, especially at the metal/wüstite interface, and at the grain boundaries where the diffusion rate is higher. Unlike the results of Gallino [18], Khramov [25] and Beck [29], no FeF x phase is observed at the metal/oxide interface or in the infiltrated salt. This is attributed to the short polarization time (maximum 1000 s compared to at least 72 h in the other studies), not long enough to allow iron fluoride formation.…”
Section: Degradation Of the Fe Y O Layercontrasting
confidence: 79%
“…This diffusion leads to the creation of pores and voids in the wüstite layer, especially at the metal/wüstite interface, and at the grain boundaries where the diffusion rate is higher. Unlike the results of Gallino [18], Khramov [25] and Beck [29], no FeF x phase is observed at the metal/oxide interface or in the infiltrated salt. This is attributed to the short polarization time (maximum 1000 s compared to at least 72 h in the other studies), not long enough to allow iron fluoride formation.…”
Section: Degradation Of the Fe Y O Layercontrasting
confidence: 79%
“…Low-melting systems based on KF instead of a conventional electrolyte decrease the working temperature by 100-150°C. These systems could lead to substantially prolonged lifetimes of the anode because of the significant reduction of the oxidation rate [1][2][3]. Towards this end, we report here our investigation of the oxidation rate of metallic anodes in the course of low-temperature aluminium electrolysis.…”
Section: Introductionmentioning
confidence: 98%
“…Among many metallic materials studied so far, Ni-Fe-Cu-based alloys appear to be promising in their ability to form a layer of nickel ferrite (NiFe 2 O 4 ) on the surface of the anode that is recognized for its low solubility in the cryolithic bath. [3][4][5] However, these alloys are sensitive to the fluoridation reaction with the cryolithic medium, forming non-conductive nickel or iron fluoride at the metal/ oxide interface, which increases the cell voltage and reduces energy efficiency of the electrolysis process. 6 It is therefore essential to remedy this problem by protecting Ni-Fe-Cu anodes with an appropriate fluoridation barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of CoO-based protective coatings for metallic anode appears promising as shown by Nguyen and de Nora. 7 However, CoO is likely to be converted into Co 3 is an n-type semiconductor that displays a significantly higher O 2 evolution overpotential than p-type semiconducting CoO. 7 It has been found that CoO can be stabilized under Al electrolysis conditions by adding about 15 wt% of Ni to form (Co,Ni)O solid solution.…”
Section: Introductionmentioning
confidence: 99%